2017
DOI: 10.1007/s10236-017-1111-y
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of equatorial deep jets in an idealised primitive equation model: an interpretation in terms of basin modes

Abstract: Ocean circulation models do not generally exhibit equatorial deep jets (EDJs), even though EDJs are a recognised feature of the observed ocean circulation along the equator and they are thought to be important for tracer transport along the equator and even equatorial climate. EDJs are nevertheless found in nonlinear primitive equation models with idealised box geometry. Here we analyse several such model runs. We note that the variability of the zonal velocity in the model is dominated by the gravest linear e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 30 publications
(75 reference statements)
0
9
0
Order By: Relevance
“…As discussed in Matthießen et al (2017), eastern and western boundaries have a strong influence on the equilibration of the zonal jets. In a basin configuration, east and west walls generate reflexion of equatorial waves.…”
Section: Influence Of Basin Modes: Long Time Scale Equilibrationmentioning
confidence: 97%
See 1 more Smart Citation
“…As discussed in Matthießen et al (2017), eastern and western boundaries have a strong influence on the equilibration of the zonal jets. In a basin configuration, east and west walls generate reflexion of equatorial waves.…”
Section: Influence Of Basin Modes: Long Time Scale Equilibrationmentioning
confidence: 97%
“…al. (; see also Matthießen et al, ) have imposed DEIV and achieved an equilibrated simulation reproducing main features of the DEC, like EDJs and EEJs. They analyzed energy transfers between waves, and they confirmed that MRG waves (from 30‐ to 100‐day period) participate in the generation of EDJs.…”
Section: Review Of Proposed Mechanisms For the Formation And Equilibrmentioning
confidence: 99%
“…In section 2, we demonstrate the mechanism first using an idealized model setup, as in Ascani et al () and Matthießen et al (, ), and then using mooring data from the equatorial Atlantic Ocean. The details of the model setup and also the treatment of the mooring data can be found in the supporting information.…”
Section: Introductionmentioning
confidence: 99%
“…The jets are well described by the gravest resonant basin mode for the dominant vertical normal mode so that the time scale of 4.5 years corresponds to the time taken by an equatorial Kelvin wave to cross the basin from west to east and then be returned as a reflected long Rossby wave to the western boundary (Cane & Moore, ). Realistic ocean models have difficulty reproducing deep jets (Ascani et al, ; Eden & Dengler, ), although they are found in idealized nonlinear primitive equation model setups where they are also well described by an equatorial basin mode (Ascani et al, , ; d'Orgeville et al, ; Matthießen et al, , ). It has been shown that the forcing for the deep jets in one such simulation is through the meridional advection term in the zonal momentum equation, with the zonal advection term acting as an energy sink (Ascani et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Their vertical scale is thought to be set by the instability, or resonant triad interaction, of intraseasonal waves (Hua et al, ) that are, in turn, excited through instabilities in the western boundary currents (d'Orgeville et al, ) or in the upper ocean currents (Ascani et al, ). Much of the variability at the equator, especially in the Atlantic, is resonant at frequencies corresponding to basin modes (Brandt et al, ; Cane & Moore, ), which is also true for the EDJ (e.g., Ascani et al, ; d'Orgeville et al, ; Matthießen et al, ; Matthießen et al, ). The period of the gravest of these resonant basin modes, T n , is set by the time it takes for a Kelvin wave to propagate across the basin, be reflected as the gravest long Rossby wave and propagate back to the western boundary, that is, Tn=4Lcn, where L is the width of the basin, n is the vertical normal mode in question, and c n is the gravity wave phase speed for that vertical normal mode.…”
Section: Introductionmentioning
confidence: 94%